Nyanyian Buaian Pada Masyarakat Kaili Tinjauan Nilai Estetika Dan Nilai Relijius - Al - afandi (Aksara: Jurnal Ilmu Pendidikan Nonformal, 2022)
This study aims to describe the aesthetic value and religious value in the cradle song of the Kaili tribe. In this study, several concepts and theories used are cultural theories that represent literary values. This study uses a qualitative descriptive method with a naturalistic approach. Sources of data obtained from informants in the field. Data collection techniques used include direct observation, recording, interviews, and recording. Data analysis used interactive analysis with three stages of analysis, namely data reduction, data presentation, and inference. The lyrics of the Kaili cradle song were collected and analyzed in this study, which consisted of four verses obtained from four different informants. The results showed that the value of the lyrics of the cradle song included aesthetic values, namely: The value of the beauty of language seen in the array of repetitions of sounds generated from rhyme by using the sound patterns a, e, i, o in the middle of the word and at the end of the word. Religious values explain the Oneness of Allah and the qualities of the apostle that must be brought to life in the child.